Equations of motions and velocities of longitudinal waves for superfluid 3He-A filled aerogel in the presence of finite magnetic field - Kekutia, Sh.E.; Chkhaidze, N.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We have determined the dynamic equations for superfluid 3He–A filled aerogel in finite magnetic fields. The speeds of propagating longitudinal modes for this system have been found for A1 and A phases. We have shown that sound phenomena in case 3He–A1 superfluid are modified from those for He II superfluid.